Nutritional and inflammatory biomarkers in predicting spontaneous anastomotic leakage closure following enterocutaneous fistula resection: the role of postoperative CRP-lymphocyte ratio - Yu, Tianchi; Liao, Xiaofeng; Luo, Shikun; Xu, Xin; Zhao, Risheng; Zhao, Yunzhao; Yao, Zheng (Frontiers in Nutrition, 2025)
BackgroundTo determine the correlation between the C-reactive protein-lymphocyte ratio (CLR) and the spontaneous resolution of anastomotic leakage (AL) subsequent to the resection of enterocutaneous fistulas (ECF).MethodsIn this retrospective cohort analysis, we examined adult patients who experienced AL following ECF resection from January 2019 to January 2024. Observations continued for 90 days post-surgery, during which CLR values were recorded at designated intervals. The relationship between CLR and the spontaneous resolution of leakage by 30 and 90 days was evaluated using logistic regression and restricted cubic splines.ResultsOut of 107 participants, 35 (32.7%) exhibited spontaneous resolution of leakage within 30 days, while 90 (84.1%) did so by the 90-day mark. A significant association was noted between CLR on day 7 post-leakage and 30-day resolution (OR = 0.97, 95%CI: 0.94–0.99, p = 0.03). Additionally, CLR on day 14 post-leakage correlated with 90-day resolution (OR = 0.88, 95%CI: 0.79–0.95, p = 0.003). A J-shaped curve was observed in the relationship between CLR levels and closure rates at both time frames. Notably, the resolution rate was considerably lower in patients whose ECF was attributable to pancreatitis, with an OR of 0.21 (p = 0.02) relative to other causes.ConclusionDecreasing CLR subsequent to leakage may be one of supportive predictor for spontaneous closure of AL following ECF resection.